PELATIHAN MANAJEMEN KEUANGAN USAHA BAGI USAHA MIKRO KECIL MENENGAH DI KELURAHAN SIDOMULYO KELURAHAN MEDAN TUNTUNGAN - Septony B. Siahaan; Dimita H. P. Purba; Mitha Christina Ginting; Lamria Sagala; Junika Napitupulu; Saur Melianna; Jeudi A.T.P. Sianturi; Kristanty M. N. Nadapdap; Gracesiela Y. Simanjuntak; Ivo M. Silitonga; Dompak Pasaribu; Mulatua P. Silalahi; Farida Sagala; Rike Y. Panjaitan; Duma Rahel Situmorang; Wesly Andri Simanjuntak; Januardi Mesakh; Sondang Ni Bulan Marbun (Universitas Methodist Indonesia, 2022)
Micro, Small and Medium Enterprises (MSMEs) are the sectors that make the greatest contribution to Indonesia's economic growth. This is due to the large number of MSMEs in Indonesia, especially North Sumatra. The presence of a large number of SMEs can create jobs and absorb labor for the environment. Micro, Small and Medium Enterprises (MSMEs) are located in Sidomulyo Village, Medan Tuntungan District, Deli Serdang Regency. MSMEs are engaged in the food and beverage sector and sell coffee, snacks and heavy meals. The facilities offered are similar to coffee shops, but simpler. MSMEs in Sidomulyo Village, Medan Tuntungan District, Deli Serdang Regency, try to limit themselves to the age of over 18 years. The implementation method used in this community service is to analyze the condition of partners, make designs, and carry out the required program planning. After all program planning is carried out, training is carried out, which is then accompanied by assistance until partners can understand and make their own financial reports using applications in Microsoft Excel. The final stage is to evaluate the financial reports that have been made by partners. The first stage carried out in community service is the discussion stage. The partners were very enthusiastic in carrying out this discussion stage, so that this discussion went well and smoothly. The next stage that is carried out after the discussion stage is assistance in inputting sales data that is written manually to be recorded simply in a bookkeeping.